The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4314/sajas.v47i5.6
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular variation in mitochondrial functionality of beef <i>semimembranosus</i>

Abstract: Intramuscular color stability variations in beef semimembranosus have been reported previously. Mitochondria remain biochemically active in postmortem muscle and can influence fresh beef color stability. However, the role of mitochondrial functionality in intramuscular color variations in beef semimembranosus is yet to be examined. We examined the functionality of mitochondria isolated from outside (OSM) and inside (ISM) regions of beef semimembranosus. Semimembranosus muscles (n = 5) were collected from insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These enzymes play a critical role in maintaining mitochondrial functionality in postmortem muscles. Moreover, several enzymes that were specific to mitochondria were detected in the sarcoplasmic fraction, indicating variation in mitochondrial degradation between the muscles (Joseph et al, 2012;Nair et al, 2017a). For example, Joseph et al (2012) reported a greater abundance of mitochondrial aconitase in the sarcoplasmic proteome of PM compared with LL, and it exhibited a negative correlation with redness.…”
Section: Application Of Proteomics In Mitochondrial Researchmentioning
confidence: 97%
“…These enzymes play a critical role in maintaining mitochondrial functionality in postmortem muscles. Moreover, several enzymes that were specific to mitochondria were detected in the sarcoplasmic fraction, indicating variation in mitochondrial degradation between the muscles (Joseph et al, 2012;Nair et al, 2017a). For example, Joseph et al (2012) reported a greater abundance of mitochondrial aconitase in the sarcoplasmic proteome of PM compared with LL, and it exhibited a negative correlation with redness.…”
Section: Application Of Proteomics In Mitochondrial Researchmentioning
confidence: 97%
“…Proteomics research demonstrated that the inner portion of the semimembranosus steaks had a greater abundance of glycolytic enzymes than their outside semimembranosus counterparts (Nair et al, 2016). Furthermore, outside semimembranosus demonstrated greater mitochondrial activity than inside semimembranosus by the end of the 4-d display (Nair et al, 2017b). Muscles with more glycolytic fibers are more color stable than muscles with oxidative fibers, which may explain animal-to-animal variation within longissimus muscles.…”
Section: Muscle-specific Differences In Color Stabilitymentioning
confidence: 98%
“…The advantage of the superficial anatomical locations et al, 2005). Furthermore, the superficial location within the SM has been reported to have greater MRA than the deep location (Seyfert et al, 2006;Nair et al, 2017). Nair et al (2017) reported the superficial portion of the top round had greater mitochondrial functionality.…”
Section: Metmyoglobin Reducing Activitymentioning
confidence: 99%
“…Furthermore, the superficial location within the SM has been reported to have greater MRA than the deep location (Seyfert et al, 2006;Nair et al, 2017). Nair et al (2017) reported the superficial portion of the top round had greater mitochondrial functionality. These findings are partially attributed to the mitochondria's role in the reduction of metmyoglobin formation.…”
Section: Metmyoglobin Reducing Activitymentioning
confidence: 99%